Interpretación del rol del personal de enfermería en el impacto psicológico del paciente quirúrgico - Pilco Díaz, Janina Gissella (2025)
The surgical process is a phase of hospitalization where depersonalization or disruption of the space of comfort and experimentation with invasive procedures generates instability, anxiety, fear and limited recovery time for the patient, thus, this research aimed to determine the importance of nursing staff in the psychological impact of the surgical patient, Therefore, a systematic review of the literature was carried out, following the methodology established by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), where 29 studies on the subject were analyzed, allowing to highlight among the main results that the nursing staff plays a fundamental role in mitigating the psychological impact on surgical patients, Therefore, personalized interventions, including emotional support, pre- and post-surgical education and effective communication, not only significantly reduce the levels of anxiety and stress in these patients but also promote a more efficient and satisfactory recovery, concluding that among the risk factors identified that predispose surgical patients to experience psychological problems, the lack of adequate information about the surgical procedure, insufficient communication with health personnel, and the lack of emotional support stand out, as the need to address these factors through clear and empathic communication, comprehensive education about the procedure and the recovery process is evidenced, emphasizing the essential role of nursing personnel in these aspects.